Analysis of Stunting Incidence Based On Food Consumpted and Environmental Sanitation - Nur Ayini S. Lalu; Juliyanty Akuba (International Journal of Hydrological and Environmental for Sustainability, 2023)
The purpose of the study was whether there was an effect on the incidence of stunting in toddlers based on the type of food consumed and environmental sanitation in Ilomata Village, Bulango Ulu District. The type of research used is quantitative research, analytic survey design. The population is 53 respondents with a sample of this study amounting to 53 respondents. Data analysis used the chi-square test. The results of the study from 53 respondents to the stunting incident were 20 respondents (37.7%). Types of food consumed in the sufficient category were the most, namely 25 respondents (47.2%). environment in the sufficient category, with the most number of 28 respondents (52.8%). The type of food consumed was in the less category, namely 13 respondents with stunting events for the stunting category, namely 13 respondents (68.4%). Environmental sanitation category is lacking, namely 16 respondents with stunting incidents for the stunting category, namely 12 respondents (75.0%). Conclusion There is an effect of stunting based on the type of food consumed. The p value = 0.002 is obtained, where the p value is smaller than Î± = 0.05. There is an effect of stunting based on environmental sanitation. The p value = 0.001 is obtained, where the p value is smaller than Î± = 0.05. It is recommended for mothers who have children under five to be more concerned about parenting and infectious diseases in children.